Evaluation of early response to hepatic arterial infusion chemotherapy in patients with advanced hepatocellular carcinoma using the combination of Response Evaluation Criteria in Solid Tumors and tumor markers. Issue 4 (April 2015) - Miyaki, Daisuke; Kawaoka, Tomokazu; Aikata, Hiroshi; Kan, Hiromi; Fujino, Hatsue; Fukuhara, Takayuki; Kobayashi, Tomoki; Naeshiro, Noriaki; Honda, Yohji; Tsuge, Masataka; Hiramatsu, Akira; Imamura, Michio; et al.
Abstract: Background and Aim: To assess the early response and outcome of hepatic arterial infusion chemotherapy (HAIC) in patients with advanced hepatocellular carcinoma (HCC). Methods: One hundred sixty‐five HCC patients treated with HAIC were reviewed retrospectively. The early response to one course of HAIC treatment was evaluated by the Response Evaluation Criteria in Solid Tumors (RECIST) and changes in α‐fetoprotein (AFP) and des‐γ‐carboxy prothrombin (DCP). Results: The median survival time (MST) for all patients was 9.5 months. The early imaging response by RECIST was assessed as partial response (PR), stable disease (SD), and progressive disease (PD) in 32 (19.3%), 86 (52.1%), and 47 (28.4%) patients, respectively. Survival correlated with early imaging response (MST in PR, 20.6; SD, 11.4; PD, 5.0 months; P < 0.0001). The MST was also significantly different in patients with AFP ratio of ≤ 1 or > 1 and DCP ratio of ≤ 1 or > 1 (worst MST, 6.5 months in patients with AFP ratio of > 1 and DCP ratio of > 1). Among patients with SD early imaging response, patients with AFP ratio of > 1 and DCP ratio of > 1 had significantly poorer survival than others (MST 7.4 vs 12.6 months, P = 0.014). The decrease in AFP and DCP in the early stage treatment with HAIC were identified as significant and independent factors associated with survival of not only all patients, but also patients with SD early imaging response. Conclusion: The use of the combination of RECIST and tumor marker ratio could be useful for assessment of the early response to HAIC and prognosis of patients with advanced HCC.